Financial Reporting Quality, Investment Efficiency, and the Role of Indonesian Sharia Stock Index (ISSI) as a Moderating Variable - Amilia Rohma; Sutrisno T; Aulia Fuad Rahman (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to examine the effect of financial reporting quality on investment efficiency and the role of Indonesian Sharia Stock Index (ISSI) as moderating. This study employed Panel Data Regression and Moderated Regression Analysis (MRA). The research population is all sector companies listed on the Indonesia Stock Exchange (IDX), with the exception of financial sector companies. Based on the purposive sampling method, 292 companies were selected as the samples (876 firm-year observations). The result of this study provides empirical evidence that the existence of financial reporting quality can increase investment efficiency (decrease overinvestment and underinvestment) using three proxies of financial reporting quality are discretionary accruals (Kothari et al 2005, discretionary accruals (Kasznik, 1999); and discretionary revenue (McNichols and Stubben, 2008). Besides that, Indonesian Sharia Stock Index (ISSI) plays a role in the positive relationship between financial reporting quality and investment efficiency using the same proxies as Hypothesis 1